If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X.2(4X-3)-8=4+2X
We move all terms to the left:
X.2(4X-3)-8-(4+2X)=0
We add all the numbers together, and all the variables
X.2(4X-3)-(2X+4)-8=0
We multiply parentheses
4X^2-3X-(2X+4)-8=0
We get rid of parentheses
4X^2-3X-2X-4-8=0
We add all the numbers together, and all the variables
4X^2-5X-12=0
a = 4; b = -5; c = -12;
Δ = b2-4ac
Δ = -52-4·4·(-12)
Δ = 217
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:X_{1}=\frac{-b-\sqrt{\Delta}}{2a}X_{2}=\frac{-b+\sqrt{\Delta}}{2a}X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-\sqrt{217}}{2*4}=\frac{5-\sqrt{217}}{8}X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+\sqrt{217}}{2*4}=\frac{5+\sqrt{217}}{8}
| 8t=7t+7 | | 96+4x+4x+(5x+2)+(5x+8)=540 | | -4.3g=25 | | x-3/x=3/12 | | -3z-1=+2-1 | | 12x+5=15x-25 | | -4+-20d=4 | | 4(x-2)-(1/5)(20x+5)=32 | | 4(5x+2)=20x-7 | | 5(x+9)=27 | | 4=1x+46 | | -5(4n+12)+2n=12(n-5) | | 3.4−0.2x=2.9+1.8x | | 6(x-2)+5=-x | | 4(x–3)+8=92 | | (2x+2)+(2x+2)+(2x+2)+(2x+2)=0 | | 11+3x-7=6x+5=3x | | -6+9p=8p | | 12−6(8u−5)=−54 | | 2-5(x+10)=6+3x | | 4(x+3.29)=11.16 | | -9p=9-8p | | 2(x+2)=110 | | -7i(-8i)=0 | | 10(-2x-3)=6(-2x-9) | | 7(4w+2)/3=-8 | | 4x-24=3x=21 | | 50+3.7=50-1.9x | | 84-12y=180 | | –6+9p=8p | | -3(7.5x)=5(1.5x) | | 3x+5+5x=25 |